Mechanical and Thermal Performances of Banana Fiber–Reinforced Gypsum Composites - Md. Abdur Rouf; Md. Rubel Alam; Shah Alimuzzaman Belal; Yeasin Ali; Md Zillur Rahman (International Journal of Polymer Science)
This study investigates the use of alkali-treated banana fibers at different weight percentages (0%, 4%, 6%, 8%, 16%, and 24%) as natural reinforcement in gypsum, aiming to assess their effects on the physical, mechanical, thermal, and morphological characteristics, as well as functional groups of composites. It is found that the density of banana fiber–reinforced gypsum composites (BFRGCs) decreases with increasing banana fiber content, reaching a minimum of 0.83 gm/cm3 at 24 wt.% fiber loading, while water absorption peaks at 98% for the same fiber loading due to the hydrophilic nature of banana fibers. Among the composites, the gypsum composite reinforced with 16 wt.% banana fiber exhibits superior mechanical characteristics, with a significantly higher tensile modulus (4.57 MPa) and flexural modulus (154.25 MPa), as well as tensile and flexural strengths of 0.81 MPa and 1.64 MPa, respectively, compared to the neat gypsum board. Further increasing fiber content to 24 wt.% results in lower tensile and flexural properties. However, adding a 24 wt.% fiber results in a substantial improvement (about 248%) in impact strength compared to the neat gypsum board. The hardness and thermal conductivity of BFRGCs reduce with increasing fiber, with the minimum hardness and thermal conductivity of 57.75 Shore A and 3.42 W/m2°C, respectively, at 24 wt.% fiber loading. Beyond 135°C, BFRGCs with 16 wt.% fiber and neat gypsum plaster lose around 15% and 19% of their mass. Scanning electron microscopy demonstrates that alkali treatment improves the fiber–gypsum interfacial bonding, whereas Fourier transform infrared spectroscopy confirms the existence of hydrogen bonds but shows minimal bond formation between the fibers and gypsum. The findings of this study provide insights into lightweight BFRGCs, highlighting their potential for applications in interior partition walls, false ceilings, decorative panels, and so on.